2017
DOI: 10.4209/aaqr.2017.04.0144
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Summertime Volatile Organic Compounds in the Lower Free Troposphere: Background Measurements at Mt. Fuji

Abstract: Air samples were collected at Mt. Fuji Research Station (FRS) for the measurements of volatile organic compounds (VOCs) in the summers of 2015 and 2016. In this study, 24 compounds were analyzed, of which only 12 halocarbons were quantified in 2015. The average total concentrations of target VOCs were 2.62 ± 1.38 and 2.99 ± 0.95 ppb in 2015 and 2016, respectively. The concentrations of individual VOCs ranged from a few ppt to a few ppb, indicating a highly inhomogeneous feature at the FRS. A cluster analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The total time required was 31.5 min. Several standard gases were used to calibrate VOCs (Ou-Yang et al, 2017). For each species, calibration was conducted and a good linear fit was observed with R 2 > 0.99.…”
Section: Chemical Analysis and Data Treatmentmentioning
confidence: 99%
“…The total time required was 31.5 min. Several standard gases were used to calibrate VOCs (Ou-Yang et al, 2017). For each species, calibration was conducted and a good linear fit was observed with R 2 > 0.99.…”
Section: Chemical Analysis and Data Treatmentmentioning
confidence: 99%
“…Alternatively, if sources are remote a low-resolution modelling approach would be more appropriate to identify air mass history (Brattich et al (2020); Sturm et al (2013)). Single back trajectory models, often driven by low-resolution meteorological input data, have been widely used to gain insight into the sampled air mass history at high-altitude sites (Keresztesi et al (2020); Brattich et al (2020); Ghasemifard et al (2019); Bolaño-Ortiz et al (2019); Qie et al (2018); Ou-Yang et al (2017); Chauvigné et al (2016); Brattich et al (2015); Gratz et al (2015); Ou-Yang et al (2014); Putero et al (2014); Tositti et al (2013); Cheng et al (2013), andFleming et al (2012) for earlier references). Advantages of this method are that it is computationally efficient, easy to perform, and for individual case studies the output is simple to interpret.…”
Section: Introductionmentioning
confidence: 99%
“…Some preview studies found that the most common pollutants in soil and groundwater contaminated by oil are total petroleum hydrocarbons (TPH), Benzene, Toluene, Xylenes, Ethylbenzene, phenol (Irie et al, 2003) and other volatile organic carbons (VOC's) that cause to damage central nervous system (Lerner et al, 2012;Hua et al, 2018;Juuti et al, 2019) of human body as well as environmental degradation. Additionally, Industries, commercial facilities, public institutions, residential households, extraction and refining of fossil fuels and biomass burning are the sources of VOCs (Ou-Yang et al, 2017;Widiana et al, 2017;Alvim et al, 2018;Hu et al, 2018). Nonetheless, a comprehensive global assessment of the nature and concentration of VOC emissions associated with rendering operations has never been undertaken (Guerra et al, 2017).…”
Section: Introductionmentioning
confidence: 99%